To Assure Pride and Confidence in the Electoral Process : Report of the National Commission on Federal Election Reform - Carter, Jimmy, 1924- (Book collections on Project MUSE., 2002)
In 2000 the American electoral system was tested by a political ordeal unlike any in living memory. Not since 1876-77 has the outcome of a national election remained so unsettled for so long. The past election's recount conundrum shook the nation's faith in the mechanisms that support the democratic process. Led by former Presidents Ford and Carter, the National Commission on Federal Election Reform undertook a study of the American electoral system. The resulting report describes where and what went wrong during the 2000 election, and makes clear and specific recommendations for reform, directed at state government, Congress, news organizations, and others. This volume also includes the full text of the Task Force Reports from the Commission.